I BRAZILIAN CONSENSUS ON MULTIMODAL TREATMENT OF COLORECTAL LIVER METASTASES. MODULE 2: APPROACH TO RESECTABLE METASTASES - RIBEIRO,Héber Salvador de Castro (2016)
Background : Liver metastases of colorectal cancer are frequent and potentially fatal event in the evolution of patients. Aim : In the second module of this consensus, management of resectable liver metastases was discussed. Method : Concept of synchronous and metachronous metastases was determined, and both scenarius were discussed separately according its prognostic and therapeutic peculiarities. Results : Special attention was given to the missing metastases due to systemic preoperative treatment response, with emphasis in strategies to avoid its reccurrence and how to manage disappeared lesions. Conclusion : Were presented validated ressectional strategies, to be taken into account in clinical practice.